Validation of the sickle scan technique used to diagnose sickle cell disease - Mihatano Barihuta, Magain; Inkalaba, Guelord; Kakumba Mankulu , Jocelyn; Nzingula, Olivier; Mbenza, Maguy Luvandu; Misengabu, Nicole M.; Ndeme, M; Diyi, Michel; Bitengeli, Mbembe; Bayebila Menanzambi, Tresor; Miezi, Nsimba; Nzunzu, José Lami; et al. (Orapuh Journal, 2025)
Introduction Sickle cell disease is a multifactorial haemoglobinopathy that causes various abnormalities in affected individuals. Several diagnostic methods exist, but most require sophisticated techniques that are not available in Congolese diagnostic centres involved in this activity. Considering the number of affected individuals in Africa, particularly in the Democratic Republic of Congo (The Democratic Republic of the Congo) (50 million people affected), and the precarious financial situation of our countries, it is essential to develop low-cost techniques to facilitate access to screening for our populations.PurposeThis study aimed to validate the rapid "Sickle SCAN" method, manufactured by ZENTECH, as a tool for rapid diagnostic testing.MethodsWe assessed a single validation criterion: selectivity. This was done using samples with known haemoglobin status. The results of the Sickle SCAN test obtained from 290 subjects were compared with those obtained through isoelectric focusing, the reference method, using the Chi-square test. The duration for trait appearance was also evaluated.ResultsThe Sickle SCAN test demonstrated 100% selectivity. Statistical analysis using the Chi-square test confirmed that the results from isoelectric focusing were identical to those obtained using the Sickle SCAN method. This test can also be applied to samples collected on blotting paper. The interpretation time should not exceed 2 minutes, contrary to the manufacturer's claims.ConclusionThe Sickle SCAN rapid screening test, manufactured by ZENTECH, produced satisfactory results and is suitable for use by the Congolese population to screen for sickle cell disease. This test has the advantages of being accessible, available, and easy to use.